PERAN KEGIATAN ESTRAKURIKULER PASKIBRA SEBAGAI UPAYA PENGUATAN KARAKTER DISIPLIN DI SMA NEGERI 21 MEDAN - Abigael Putra Siallagan; Hapni Laila Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Your research aims to find out how the extracurricular activities of Paskibra in forming the character of discipline and understand what are the supporting and inhibiting factors of this Paskibra activity in fostering the character of discipline of students at SMA Negeri 21 Medan. The research uses a qualitative method with a qualitative descriptive approach. The qualitative descriptive approach is a research method that combines qualitative and descriptive approaches. This method is used to describe certain phenomena, events, or circumstances, it is hoped that it can understand how the existence of Paskibra extracurricular activities as an effort to strengthen the character of discipline. The data used in this study include primary data and secondary data. Data collection techniques used through direct interviews, field observations, and documentation. Data analysis techniques use qualitative, which consist of data induction, data presentation, and data verification or drawing conclusions. The results of the study show that student discipline at SMA Negeri 21 Medan still faces various problems, mainly due to low personal awareness, less positive environmental influences and minimal family and school support in instilling the value of discipline. Paskibra extracurricular activities have proven to be an important forum in building the character of discipline through regular practice. habituation, responsibility, and strengthening of group work. The success of this program is further supported by adequate facilities, the commitment of the instructors, and the support of the school, although there are still obstacles in the form of limited active members, limited practice time, and differences in student motivation. Therefore, more creative and sustainable Paskibra management is needed so that discipline development can take place optimally and reach all students.